KARAKTERISASI ALIRAN GAS-CAIR FLUIDA VISKOS SEARAH PADA BELOKAN PIPA HORISONTAL - Muhajir, Khairul (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2006)
ABSTRACT This study aims to discover the pressure distribution as well as flow patterns taking place at a U-pipe bend with the elbow angle (j) of 180o and oblique angle variations (q) of 0o or horizonta. The study was conducted using air-glycerine flow at room temperature (27oC – 30oC). Air flow rates have four variations (2,3599E-05; 3,9331E-05; 5,5064E-05; 7,0796E-05) m3/s and glycerine flow rates have five variations (4,101E-04; 4,921E-04; 5,741E-04; 6,561E-04; 7,381E-04) m3/s. At first, glycerol was channelled with constant flow, then air was channelled with the first flow until fourth flow. Then glycerol flow was raised from the second to fifth flow, while air flow starting from first flow to fourth flow, respectively. The test section diameter is 25 mm and the bend radius is 175 mm, or R/D = 7.The study results indicated that on the single-phase flow, the greatest pressure distribution occurred on the outer side, specially on the bank position the greatest pressure distribution was on the bottom side bend, while for the two-phase flow the greatest pressure distribution also occurred on the outer wall and specially on the bank posision the greatest pressure distribution was on the top side bend. Flow patterns occurred are bubble flow, plug flow, stratified flow, stratified wave flow, slug flow, and annular flow. This reseach to show that in two phase viscous fluid flow must be don’t use the U pipe bend in order to prevent the losses.